(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article discusses the cultural approach and guidelines for its use in the process of literary education. The formation of cultural education as a term is considered in historical aspects. The polysemantic aspects of the term and the tendencies of spiritual closeness are theoretically justified in the views of a number of scientists. Also, the advantages of using a cultural approach and its importance in forming an effective educational environment are proven with the help of practical examples.